INTERROGATING THE SOCIAL PSYCHOANALYTIC - Young, Lisa Saville (PINS-Psychology in Society, 2025)
Gülerce, Aydan (ed) (2012) Re(con)figuring psychoanalysis: Critical juxtapositions of the philosophical, the sociohistorical and the political. Houndmills: Palgrave Macmillan. ISBN 978-0-230-29375-5 hbk. Pages xv + 283. This edited volume is a welcome addition to a growing body of work that aims to employ psychoanalysis “outside of the clinic” (Frosh, 2011) to rework philosophical, social, historical and political issues of our contemporary world. The contributions demonstrate how psychoanalysis can be taken up to relook at socio-historical issues relevant to our lives, from the use of metaphors in the Philippines to attendance at a psychoanalytic congress, from HIV/AIDS to motherhood, and violent crime in South Africa. As such, this book belongs firmly in the Psychosocial Studies library, where the semantically separated “social” and “psychical” are re-visioned through a particular binocularity (Frosh & Saville Young, 2008). Certainly, the focal point is psychoanalysis, as the title suggests, which the contributors demonstrate is particularly rich in conceptual and theoretical tools to aid us in this psychosocial vision. Significantly too, Gulerce argues that the authors offer not only re-visions of issues relevant to our current lives but re-visions of psychoanalysis itself, and perhaps it is precisely this call for a critical relook of psychoanalysis itself, alongside its employment, that makes this work engaging and productive.